Assessment of Efficacy of Supraintercondylar and Supracondylar Femur Fractures Treated with Condylar Buttress Plates: A Comparative Study - Deoda, Yusuf Ali; Garhwal, Prashant (Asian Journal of Medical Research, 2019)
Background: Treatment of supraintercondylar and supracondylar femur fractures is generally challenging. This study was conducted to compare the efficacy of supraintercondylar and supracondylar femur fractures treated with condylar buttress plates. Subjects and Methods: The study was conducted in Department of Orthopaedics, Government S K Hospital, Sikar, Rajasthan, India. The sample size of 50 patients was selected for the study. Participants of age above 21 were included in the study. Among these in group I, there were 25 participants of supra intercondylar fractures whereas in group II , 25 participants of supra condylar fractures. Statistical analysis was done by using SPSS, version 22 (SPSS, Inc., Chicago, IL) and p<0.05 was considered statistically significant. Results: In our study, 32 were males whereas 18 were females. Supra intercondylar fractures were present in 17 males and 8 females whereas supra condylar fractures were present in 15 males and 10 females. Rate of union occur in 23 cases of Supra intercondylar fractures whereas in 24 cases supra condylar fractures. Complications such as stiffness, varus deformity occur more in supra intercondylar fractures. Time taken for union in both the cases are almost same. Conclusion: Our study concludes that clinical results of supracondylar fractures was better with condylar buttress plates as compared to supra intercondylar fractures.